Schizophrenia treatment preferences of psychiatrists versus guidelines: A European perspective - Martina Rojnic Kuzman; Merete Nordentoft; Andrea Raballo; Pavel Mohr; Andrea Fiorillo; Geert Dom; Goran Mihajlovic; Tihana Jendricko; Egor Chumakov; Stojan Barjaktarov; Bernardo Carpiniello; Michal Patarák; et al. (European Psychiatry)
Abstract Background We aimed to identify therapeutic approaches for managing schizophrenia in different phases and clinical situations – the prodromal phase, first-episode psychosis, cognitive and negative symptoms, pregnancy, treatment resistance, and antipsychotic-induced metabolic side effects – while assessing clinicians’ adherence to guidelines.